Chapter Analysis of the limits for the detection of small garbage island immersed in clutter radar - Serafino, Francesco (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This work show the limits of the detection capacity of X-band radars, as the sea state changes, in order to identify, discriminate, characterize and track small floating aggregations of plastic marine litter (Small Garbage Island - SGIs). Two distinct radar measurement campaigns were conducted at sea of SGI modules assembled in the laboratory. The measurement were carried out respectively in conditions of calm sea, to test the system in ideal conditions, and in rough sea conditions. The data analysis confirmed the ability of the X-band radars to detect the aggregations of floating waste on the sea surface.